2015
DOI: 10.1002/fut.21722
|View full text |Cite
|
Sign up to set email alerts
|

Long Memory in Asymmetric Dependence Between LME and Chinese Aluminum Futures

Abstract: The co-dependence of many asset returns has been shown to be asymmetric and to follow long memory dynamics in recent studies. To capture the two features simultaneously, based on Hafner and Manner (2012), we propose the new model of fractionally integrated stochastic copula allowing for long memory in the evolution of co-dependence. In the empirical analysis, the aluminum futures markets of London Metal Exchange and Shanghai Futures Exchange were shown to have stronger co-dependence in market downturns than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Since then, numerous studies have investigated price discovery in informationally linked markets (see H. Chen, Choi, & Hong, 2013; Gonzalo & Granger, 1995; Hasbrouck, 1995; Rapach, Strauss, & Zhou, 2013; Ye, 2014). In global futures trading, it has been found that preeminent exchanges take the lead in price discovery for certain commodities (see Covrig, Ding, & Low, 2004; Gong & Zheng, 2016; Han, Liang, & Tang, 2013; Jiang, Su, Todorova, & Roca, 2016; Liu & An, 2011; Yin & Han, 2013). Given this, how should newer entrants behave, particularly when setting trading hours?…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous studies have investigated price discovery in informationally linked markets (see H. Chen, Choi, & Hong, 2013; Gonzalo & Granger, 1995; Hasbrouck, 1995; Rapach, Strauss, & Zhou, 2013; Ye, 2014). In global futures trading, it has been found that preeminent exchanges take the lead in price discovery for certain commodities (see Covrig, Ding, & Low, 2004; Gong & Zheng, 2016; Han, Liang, & Tang, 2013; Jiang, Su, Todorova, & Roca, 2016; Liu & An, 2011; Yin & Han, 2013). Given this, how should newer entrants behave, particularly when setting trading hours?…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a related issue concerns whether price movements across exchanges are symmetric or exhibit different behavior for upturns than downturns in prices. Gong and Zheng () examine aluminum futures trading on the Shanghai Futures Exchange and London Metals Exchange and report evidence of “stronger co‐dependence in market downturns than in upturns.”…”
Section: Where Is Price Discovery Occurring?mentioning
confidence: 99%